To catheterise or not to catheterise? An approach based on decision theory. Issue 3 (March 1984) - Macartney, F; Douglas, J; Spiegelhalter, D
Abstract : To determine whether or not patients require cardiac catheterisation before surgery a computer based mathematical model was constructed based on decision theory. The model was specifically applied to sick infants under 3 months of age with suspected coarctation of the aorta, and a three way sensitivity analysis was carried out to assess the effects on the model of changes in the probabilities that underlie the decision itself. The optimal decision (that with the greater survival rate) was moved away from cardiac catheterisation to confirm the diagnosis towards operating without cardiac catheterisation by the following factors: a higher probability of survival of operation both in the presence and absence of coarctation; a higher probability of survival if there was no coarctation and no operation performed; a lower sensitivity of catheterisation; a greater incremental risk of operation resulting from previous catheterisation; and a higher relative risk of catheterisation in patients without as opposed to with coarctation. Factors that tended significantly to move the decision towards catheterisation to rule out coarctation rather than neither to operate nor to catheterise were: a lower risk of surgery for coarctation if present; a higher risk of failing to operate on a patient who had coarctation; a high specificity of cardiac catheterisation; a lower incrementation of surgical risk by previous cardiac catheterisation; and a lower relative risk of catheterisation if coarctation was absent. In this institution, the model argues strongly against cardiac catheterisation in the great majority of sick infants with coarctation.